Realm of algebra - Asimov, Isaac, 1920- (London : Victor Gollancz Ltd., 1964)
An introduction to the basic theory and concepts of algebra along with a detailed explanation of more complicated equations and a brief discussion of the many uses of algebra in our lives.
Keywords: Algebra